Hipertiroidismo na Gravidez – um Caso Clinico - Ribeiro, F (2012)
Thyroid disease is common in pregnant women.We report a 10 weeks gestation pregnancy with hyperemesis gravidarum, hypertension crisis and hyperthyroidism